Improving The Ability Of Writing Review Texts Through The Concept Sentence Learning Model Class VIII-1 Students Of SMP Negeri 2 Tuhemberua - Bina Sadarmawati Telaumbanua (Indonesian Journal of Education and Mathematical Science, 2021)
Review text is a text that results from an analysis of various things. Analysis can take the form of books, novels, news, reports or fairy tales. The text provides responses or analyzes related to the setting, time, place, and characters in the text. Basically, the review text is a book review or summary. The purpose of this study was to improve the students' ability to write text reviews using the Concept Sentence learning model. This classroom action research activity was carried out in two cycles using data collection techniques, observation sheets and assessment sheets. The subjects of this study were students of class VIII-1 SMP Negeri 2 Tuhemberua in the even semester, totaling 26 students, with 15 boys and 11 girls. The results of this study indicate that there is an increase in the ability to write reviewed texts through the concept sentence learning model. Cycle I with an average value of 62.11 the lowest score is 50, the highest score is 80, while in the second cycle with an average value of 80 the lowest score is 75 the highest score is 90. Students who complete the first cycle are 9 people with an average percentage 34.6% while the students who completed the second cycle were 26 people with an average percentage of 100%. The results of student observations in the first cycle of the first meeting were 76.15% and the second meeting was 79.23%, whereas in the second cycle the first meeting was 85.38% and the second meeting was 93.46%. The results of observations on the performance of researchers in the first cycle of the first meeting were 57.89% and the second meeting was 72.36%, while the second cycle of the first meeting was 81.57% and the second meeting was 88.15%. Based on the results of the study, the researchers concluded that: using the Concept Sentence learning model can improve the ability to write review texts in class VIII-1 students of SMP Negeri 2 Tuhemberua in the Learning Year. Suggestions from these results, the researchers suggest that: 1) for students it is expected to be able to increase interest in writing review texts, 2) for teachers of SMP Negeri 2 Tuhemberua, this research can enrich the knowledge of teachers in the field of study in solving problems related to teacher efforts. in improving the skills of SMP Negeri 2 Tuhemberua.